Bioformation of N-Acetylglucosamine from Shrimp Shell Chitin by Serratia marcescens PT-6 Cultured in various pH and Temperature - Bekti Wulan Sari; Nurul Binti Isnaini; Indun Dewi Puspita; Amir Husni; Ustadi Ustadi (Universitas Gadjah Mada, 2017)
The study aimed to determine the effect of pH and temperature on N-Acetylglucosamine (NAG) formation from shrimp shell chitin by Serratia marcescens PT-6 fermented in chitin broth medium. Parameters examined on NAG formation include bacteria growth, chitinase activity (U/ml), and NAG concentration in medium (mg/ ml). Bacteria growth was measured by turbidity (OD600), while chitinase activity and NAG concentration in the medium were analyzed quantitatively by colorimetric assay. The variation of initial pH examined in chitin broth medium was 5; 6; 7; 8, while temperature variation was 30°C; 37°C; dan 40°C. The results show that maximum concentration of NAG formed by Serratia marcescens PT-6 was 33.86 µg/ml on day-3 of fermentation, at pH 7 and temperature of 30°C. Chitinase activity on the same day was 0.002 U/ml, while OD600 value of the culture was 0.42 indicating the bacteria were in the log phase. This research implies that Serratia marcescens PT-6 is potential to be optimized further for the bioconversion process of NAG from shrimp shell waste through an enzymatic method by modifying its culture condition.